Hak Korban untuk Menuntut Restitusi Akibat Tindak Pidana Korupsi Tertentu - Supanto Supanto; Sulistyanta Sulistyanta; Ismunarno Ismunarno; Winarno Budyatmojo; Tika Andarani Parwitasari; Budi Setyanto; Sabar Selamet (Universitas Muhammadiyah Purwokerto, 2022)
AbstractThere is a government program for the poor in the COVID-19 pandemic situation. People who receive assistance have the right to control as a form of transparency (Law 14 of 2008 concerning Openness of Public Information) so that people are not just objects. The public generally plays a preventive role in overcoming corruption. However, the judge's decision has not been touched on the Crime of Corruption (Tindak Pidana Korupsi, TIPIKOR). Especially when the community members are in a position as